Social Networks as a Coping Strategy for Food Insecurity and Hunger for Young Aboriginal and Canadian Children - Benita Tam; Leanne Findlay; Dafna Kohen (Societies, 2014)
Traditional foods and food sharing are important components of Aboriginal culture, helping to create, maintain, and reinforce social bonds. However, limitations in food access and availability may have contributed to food insecurity among Aboriginal people. The present article takes a closer examination of coping strategies among food insecure households in urban and rural settings in Canada. This includes a comparative analysis of the role of social networks, institutional resources, and diet modifications as strategies to compensate for parent-reported child hunger using national sources of data including the Aboriginal Children’s Survey and the National Longitudinal Survey of Children and Youth. Descriptive statistical analyses revealed that a majority of food insecure urban and rural Inuit, Métis, and off-reserve First Nations children and rural Canadian children coped with hunger through social support, while a majority of urban food insecure Canadian children coped with hunger through a reduction in food consumption. Seeking institutional assistance was not a common means of dealing with child hunger, though there were significant urban-rural differences. Food sharing practices, in particular, may be a sustainable reported mechanism for coping with hunger as such practices tend to be rooted in cultural and social customs among Aboriginal and rural populations.